Physical Harm Reduction in Domestic Violence: Does Marijuana Make Assaults Safer? - Kaplan, Jacob (Journal of interpersonal violence, 2022)
Studies on the effect of marijuana on domestic violence often suffer from endogeneity issues. To examine the effect of marijuana decriminalization and medical marijuana legalization on serious domestic assaults, we conducted a difference-in-differences analysis on a panel dataset on NIBRS-reported assaults in 24 states over the 12 years between 2005 and 2016. Assaults disaggregated according to situation and extent of injury were employed as dependent variables. We found that while the total number of assaults did not change, decriminalization reduced domestic assaults involving serious injuries by 18%. From a harm reduction perspective, these results suggest that while the extensive margin of violence did not change, the intensive margin measured by the seriousness of assaults were substantially affected by decriminalization. This result may be partially explained by reductions in offender alcohol intoxication and weapon-involved assault.